IL-17A drives a fibroblast-neutrophil-NET axis to exacerbate immunopathology in the lung with diffuse alveolar damage - Su, Duo; Li, Lu; Xie, Hao; Ai, Lingli; Wang, Yuqing; Yang, Bo; Zhou, Dongsheng; Hu, Lingfei; Yang, Huiying (Frontiers in Immunology, 2025)
Diffuse alveolar damage (DAD), a lethal manifestation of acute lung injury, remains a critical public health concern due to the absence of targeted therapies. However, the underlying cellular and molecular mechanisms responsible for immunopathology during DAD progression are largely undefined. Here, by integrating single cell RNA sequencing, functional assays, and genetic/pharmacological interventions in a mouse model of ricin-induced DAD, we revealed a significant accumulation of neutrophil with an activated phenotype that plays a critical role in immunopathology. We observed the formation of neutrophil extracellular traps (NETs) during DAD, which further intensified inflammation and tissue injury. IL-17A signaling activity was upregulated in DAD-affected lungs, while IL-17A deficiency or functional blockade significantly attenuated neutrophil recruitment, NET generation, and tissue damage. Mechanically, IL-17A stimulates lung resident fibroblasts to produce the neutrophil chemoattractant CXCL1. Notably, type 3 innate lymphoid cells (ILC3) emerged as the dominant source of IL-17A, highlighting a triad of interactions among ILC3, fibroblast, and neutrophil in DAD pathogenesis. This finding delineates a pathogenic IL-17A-neutrophil-NET axis that amplifies lung immunopathology after ricin-induced DAD, a deeper understanding of these relationships may pave the way for mitigate DAD immunopathology and other lung inflammatory disorders.